Atividade antiulcerogênica e anti-inflamatória intestinal do estragol em modelos animais - Alves Júnior, Edvaldo Balbino (2023)
Phenylpropanoids are a class of compounds produced by medicinal plants and are biosynthesized from phenylalanine via cinnamic acid. Estravole is a phenylpropanoid that is present as a constituent of essential oils of many plant species, such as Ravensara anisata (Madeira), Ocimum basilicum (Basil) and Croton zehntneri (Cinnamon). Pharmacological activities such as antioxidant, antimicrobial, anxiolytic, skeletal muscle contractile, visceral muscle relaxant, anti-inflammatory and gastroprotective are described. The present work has the general objective to evaluate the intestinal antiulcerogenic and anti-inflammatory activity of trazol in animal models. In the cysteamine-induced duodenal ulcer model, oral (v.o) administration of trazol at doses of 31; 62; 125 and 250 mg/kg) reduced (p<0.001) the ulcerative lesion area (ALU) in rat duodenum. From the gastric ulcer protocol induced by acetic acid, the toxicity was investigated by repeated doses for 14 days. The results showed that the treatment (v.o) with 250 mg/kg of trazol reduced (p<0.001) the ALU, when compared to the control group. This effect was related to an increase in the levels of GSH, SOD, IL-10 and TGFβ (p<0.001) and a reduction (p<0.001) in the levels of MDA, MPO, IL-1β, TNF-α and NFκB. The administration of trazol for 14 days did not change the weight of the organs (heart, liver, spleen and kidneys), nor the biochemical and hematological parameters evaluated. In addition, the test substance protects the animals from reduced water and feed consumption. In the acute induction model of TNBS-induced intestinal inflammation, trazol reduced (p<0.05) the macroscopic lesion score, ALU, weight/length ratio, and diarrheal index at all doses evaluated. In the sub-chronic protocol of ulcerative colitis with relapse, the most effective dose of trazol (250 mg/kg) reduced (p<0.01) the macroscopic lesion score, the ALU and the colonic weight/length ratio. From the acute and sub-chronic colitis protocols, it was observed that trazol (250 mg/kg) reduced (p<0.001) MDA and MPO levels and restored GSH and SOD levels. In addition, it reduced (p<0.001) levels of IL-1β, TNF-α and NFκB, as well as increased TGFβ levels (p<0.001) and restored (p<0.01) IL-10 levels. In the evaluation of the epithelial barrier function, an increase (p<0.001) of the immunostaining for zone of occlusion-1 (ZO-1) was shown. Based on the data analyzed, it can be suggested that trazol has anti-duodenal ulcer activity, gastric healing activity is related to the induction of re-epithelialization of the lesion and low toxicity by repeated doses. And intestinal anti-inflammatory activity in the acute and sub-chronic phase, being related to the cytoprotection of the intestinal barrier through the preservation of gap junctions, antioxidant system and immunomodulation.